ChemInform Abstract: Growth of Boronic Acid Based Two‐Dimensional Covalent Networks on a Metal Surface under Ultrahigh Vacuum. Issue 38 (10th September 2014) - Clair, Sylvain; Abel, Mathieu; Porte, Louis
Abstract Review: 79 refs.